Britain and the German Churches, 1945-1950 : the role of the Religious Affairs Branch in the British zone - Howson, Peter (Woodbridge : The Boydell Press, 2021)
Explores the ways in which the British Religious Affairs Branch aimed to organise religious life in post-war Germany.
Title from publisher's bibliographic system (viewed on 26 Mar 2021).
Keywords: Germany (Territory under Allied occupation, 1945-1955 : U.S. Zone). -- Office of Military Government. -- Internal Affairs and Communications Division. -- Education and Religious Affairs Branch; Christianity and politics -- Germany -- History -- 20th century; Church and state -- Germany -- History; Germany -- Religious life and customs